2016
DOI: 10.1080/13102818.2016.1261636
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of different types of COH protocols for in vitro fertilization at national level

Abstract: The aim of this study was to retrospectively analyse the cost-effectiveness of different types of controlled ovarian hyperstimulation (COH) protocols and regimes used in in vitro fertilization procedures at a national level. Information was gathered from the National Centre for Assisted Reproduction (Bulgaria). Out of 2849 patients, 2757 were included in the study. The patients were treated with three main protocols: gonadotrophin-releasing hormone (GnRH)-antagonist protocol, GnRH-agonist protocol and COH prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Comparing our results with those of the previous studies is limited, because the latter had less strict inclusion criteria (e.g., including not only poor responders), a different design (e.g., trial-based and model based economic evaluations), different perspectives (e.g., costs related to sick leave, obstetric and post-natal costs of live births), and different outcomes (e.g., pregnancy within 1 year leading to term live birth). However, one study found no difference in pregnancy rate between the two treatment protocols (Polinder et al, 2008), while the other two studies showed that the MS-IVF was more effective than C-IVF (Crawford et al, 2016;Benbassat et al, 2017). Overall, our findings are in line with their conclusions, namely that MS-IVF is more likely to be cost-effective than C-IVF.…”
Section: Comparison With Other Effectiveness Studiessupporting
confidence: 88%
See 3 more Smart Citations
“…Comparing our results with those of the previous studies is limited, because the latter had less strict inclusion criteria (e.g., including not only poor responders), a different design (e.g., trial-based and model based economic evaluations), different perspectives (e.g., costs related to sick leave, obstetric and post-natal costs of live births), and different outcomes (e.g., pregnancy within 1 year leading to term live birth). However, one study found no difference in pregnancy rate between the two treatment protocols (Polinder et al, 2008), while the other two studies showed that the MS-IVF was more effective than C-IVF (Crawford et al, 2016;Benbassat et al, 2017). Overall, our findings are in line with their conclusions, namely that MS-IVF is more likely to be cost-effective than C-IVF.…”
Section: Comparison With Other Effectiveness Studiessupporting
confidence: 88%
“…However, one study found no difference in pregnancy rate between the two treatment protocols ( Polinder et al. , 2008 ), while the other two studies showed that the MS-IVF was more effective than C-IVF ( Crawford et al , 2016 ; Benbassat et al , 2017 ). Overall, our findings are in line with their conclusions, namely that MS-IVF is more likely to be cost-effective than C-IVF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations